2021
DOI: 10.1186/s12909-021-02695-8
|View full text |Cite
|
Sign up to set email alerts
|

A multicentric study on stigma towards people with mental illness in health sciences students

Abstract: Background There is evidence of negative attitudes among health professionals towards people with mental illness but there is also a knowledge gap on what training must be given to these health professionals during their education. The purpose of this study is to compare the attitudes of students of health sciences: nursing, medical, occupational therapy, and psychology. Methods A comparative and cross-sectional study in which 927 final-year studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 39 publications
2
32
2
Order By: Relevance
“…The overall results from this study show that some level of stigma towards people with mental illness is present across all dimensions of stigma, which is in line with previous studies that also found explicit stigma in nursing students regarding people with mental illness [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The overall results from this study show that some level of stigma towards people with mental illness is present across all dimensions of stigma, which is in line with previous studies that also found explicit stigma in nursing students regarding people with mental illness [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…Nursing students share the same misconceptions towards people with mental illness as the general public, and those with a high level of stigma often display discomfort, anxiety and fear when caring for people with mental illness [17,18]. In fact, a recent study identified stigmatised misconceptions about people with mental illness in nursing students, such as the assumption of them being dangerous and having worse prognoses [19]. Other studies also identify that nursing students believed that people with mental illness needed to be segregated from the community [20,21] and had more difficulty expressing compassion for those patients [20].…”
Section: Introductionmentioning
confidence: 99%
“…The study of stigmatizing behavior directed towards PLWHA among medical students can be valuable to reveal the defects and gaps in medical education and clinical training courses [ 15 , 16 , 17 ]. This can be related to the previous evidence showing that lack of adequate skills and improper training might be associated with fear and avoidance, and subsequent negative attitude [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A worldwide online survey across 65 countries showed that stigma toward both psychiatry and psychiatric patients was common among undergraduate medical students [ 13 ]. Medical students and nursing students believed that people with mental disorders symbolized aggression as well as unpredictability, and would never be able to recover sufficiently [ 14 ]. Furthermore, medical and nursing students would like to evaluate working in a psychiatric department job as stressful, overwhelming, emotionally and exhausting, even daunting [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%